2021
DOI: 10.3390/su13020656
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Municipal Waste Recycling and Renewable Energy Consumption on CO2 Emissions across the European Union (EU) Member Countries

Abstract: The world population maintains a growing trend and in turn, the amount of municipal waste is also increasing. Rising municipal waste quantity poses a challenge for human beings and the environment, therefore recycling becomes important for environmental sustainability and circular economy. This study explores the effects of municipal waste recycling and renewable energy on the environment sustainability proxied by CO2 emissions in EU member states over the period from 2004 to 2017 through panel cointegration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 28 publications
(47 reference statements)
0
17
0
Order By: Relevance
“…The second strand of research focuses on the economic growth and environmental pollution nexus [11,17,[49][50][51][52][53][54]. This branch of research attempts to verify the environmental Kuznets curve (EKC) hypothesis [4,10,11,43,53].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The second strand of research focuses on the economic growth and environmental pollution nexus [11,17,[49][50][51][52][53][54]. This branch of research attempts to verify the environmental Kuznets curve (EKC) hypothesis [4,10,11,43,53].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another perspective including an assessment of long-term and short-term correlations between renewable energy use, CO 2 emissions and municipal waste recycling has been provided in a study published by Bayar et al [52]. The findings of that study showed no significant correlation between recycling rate, renewable energy and CO 2 emissions.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Waste-to-energy (WTE) incineration projects are one kind of biomass power generation, which is considered resource-friendly and environment-friendly [1] and thus promoted by government authorities in the face of global climate change [2]. It is an important component of renewable energy, which could facilitate the optimization of the energy structure [3,4], the reduction of carbon dioxide emissions [5][6][7] and the promotion of economic growth [8]. WTE plants are widely adopted in a lot of countries and regions, including Accra of Ghana [9], Malaysia [10][11][12], Europe Union [13], Italy [14], Taiwan [15], Indonesia [16], Vietnam [17], Mainland China [18] and New Zealand [19].…”
Section: Introductionmentioning
confidence: 99%
“…Empirical results revealed a positive and significant association with financial development. Bayar et al (2021) described the association of municipal wastage, recycling energy, renewable sources of energy, energy usage with CO2 in European Union nations. The employed cointegration and casualty analysis were employed during 2004-2017.…”
Section: Introductionmentioning
confidence: 99%